Identifikasi tutupan vegetasi dan potensi fisik lahan untuk pengembangan ekowisata di laboratorium lapangan konservasi sumberdaya hutan dan ekowisata hutan pendidikan Unhas - Amran Achmad; Putu Oka Ngakan; Anwar Umar; Asrianny (Jurnal Penelitian Kehutanan Wallacea, 2012)
The aims of this study are to identify vegetation coverage and physical potential of land that can be developed as an ecotourism attraction, and plan for the management of ecotourism development space in the Field Laboratory of Forest Resources Conservation and Ecotourism, Unhas Educational Forest. Vegetation cover, was interpreted from satellite images by using remote sensing techniques, while the physical land potential data information was collected through direct measurements in the field by using GPS, compass and meter. Data analysis was done by using GIS with overlay method and Digital Elevation Model (DEM). The results showed that the Field Laboratory of Forest Resources Conservation and Ecotourism, Unhas Educational Forest, has natural forest vegetation and pine plantations forest covering 91.32% of the total land area of 311 ha, that potentially for the development of ecotourism. Some interesting physical potential to be developed as an ecotourism attraction, is a waterfall, mountain peaks, camping ground and a research station.